Natural Eutectic Solvent-Based Temperature-Controlled Liquid–Liquid Microextraction and Nano-Liquid Chromatography for the Analysis of Herbal Aqueous Samples - Álvaro Santana-Mayor; Giovanni D’Orazio; Miguel Ángel Rodríguez-Delgado; Bárbara Socas-Rodríguez (Foods)
In this work, two novel (-)-menthol-based hydrophobic natural eutectic solvents with vanillin and cinnamic acid were prepared and applied as extraction solvents. In this regard, 12 endocrine disruptors, including phenol, 2,4-dimethylphenol, 2,3,6-trimethylphenol, 4-tert-butylphenol, 4-sec-butylphenol, 4-tert-amylphenol, 4-n-hexylphenol, 4-tert-octylphenol, 4-n-heptylphenol, 4-n-octylphenol, and 4-n-nonylphenol and bisphenol A, were studied in a green tea drink. A temperature-controlled liquid–liquid microextraction was used as the extraction method, and nano-liquid chromatography–ultraviolet detection was used as the separation and determination system. Different parameters affecting the compatibility of the non-ionic eutectic solvents with water-polar organic solvent mixtures and chromatographic and detection systems were optimized, including injection/dilution solvent, injection mode, mobile phase composition, and step gradient. With the same purpose, two stationary phases were tested, including XBridge® C18 and a mixed-phase Cogent C30-XBridge® C18. Finally, the greenness and blueness of the methodology were assessed to evaluate the environmental profile and usability of the procedure.